Monitoring and Evaluation of the Anticorruption Reforms - Kolaković-Bojović, Milica (Zbornik Instituta za kriminološka i sociološka istraživanja, 2019)
Establishing effective mechanisms for monitoring and evaluation of anticorruption reforms is one of the key preconditions to avoid that numerous strategic documents and concrete reform measures planned by these documents are only a "dead letter", but also to ensure their implementation in a way that produces the desired effects in society. Starting from this assumption, the author analyzes in detail the development, structure, method of functioning, as well as the results of the implementation of monitoring mechanisms that have been established in the Republic of Serbia in the field of anticorruption in the last two decades. The paper has in its focus both the competencies of the key institutions in this field as well as the specialized, permanent and temporary working bodies of the Government, established with the aim of monitoring the implementation of key strategic documents. The author pays particular attention to problems related to the unclear delineation of the roles and responsibilities of institutions and working bodies in these processes, as well as the effects that the parallel functioning of multiple monitoring mechanisms has on the efficiency of implementing reforms. The author analyzes the perspectives of solving the observed problems and further improvement of the whole system in light of the adoption of the Law on Prevention of Corruption and the revision of the Action Plan for Chapter 23.